Heritage Keepers: the perils in textile conservation - Pinheiro, Ana Catarina (2021)
One of the most frequent professional afflictions in Conservators-Restorers is the onset of work-related musculoskeletal disorders (WMSDs). The conservation of textiles is recognizably vulnerable to these problems. However, the assessments of the ergonomic conditions for these workers are rare or even non-existing. The present study focuses on a group of conserva-tors-restorers of textiles and relies on the use of a Nordic Questionnaire for musculoskeletal dis-orders coupled with a Quick Exposure Check for the task of consolidation on a horizontal table to determine the severity and exposure levels to WMSDs. All surveyed workers reported numbness, pain or discomfort in the last 12 months for the neck region, while 67% reported the same afflic-tions for the back, shoulders/arms and hands/wrist. In the same time period, half of the workers have used pain relievers in order to maintain their professional activity. For the textile consolida-tion task, the neck and back areas showed high and very high levels of exposure (respectively) and the results place these workers at a high-risk for WMSDs due to cumulative stress. Mitigation strategies are proposed but these should be paired with professional counseling. Although pre-liminary, this study is the first of its kind to assess the ergonomic impact of the profession in Por-tugal and presents a methodology that can be used to perform similar evaluations in other work-places and/or other specialties in the Conservation and Restoration sphere, both nationally and internationally.